RELIGIUSITAS DAN KECENDERUNGAN MELAKUKAN KEKERASAN DALAM RUMAH TANGGA - Rahmah, Zulfa; Syafrilsyah, Syafrilsyah; Fatmawati, Fatmawati (Faculty of Ushuluddin and Humanities, 2020)
Family is the smallest unit of the organization which can develop someone's character. Every human being hopes to have tranquility, affective, and merciful family. However, domestic violence case is increasing each year. It is the sign that human beings' morality is decreasing day by day as well as a misunderstanding of religious teachings. Thus, this study aimed to find out the relationship between religiosity and the tendency of committing domestic violence among husband in Banda Aceh city. This study used a quantitative method with a purposive sampling technique. The participants recruited were 120 husbands. The result showed there was a negative and significant relationship between religiosity and the tendency of committing domestic violence among husband in Banda Aceh city with Pearson correlation value r= -0,788, p= 0,00 (p=<0,05). The finding of this study implied that religiosity has a significant contribution toward the tendency of committing domestic violence in the family. Hence, understanding religious teaching is significantly needed for achieving a peaceful family.